CD74-NRG1 fusions in lung adenocarcinoma - Fernandez-Cuesta, Lynnette; Plenker, Dennis; Osada, Hirotaka; Sun, Ruping; Menon, Roopika; Leenders, Frauke; Ortiz-Cuaran, Sandra; Peifer, Martin; Bos, Marc; Daßler, Juliane; Malchers, Florian; Schöttle, Jakob; et al. (Cancer discovery, 2014)
We discovered a novel somatic gene fusion, CD74-NRG1, by transcriptome sequencing of 25 lung adenocarcinomas of never smokers. By screening 102 lung adenocarcinomas negative for known oncogenic alterations, we found four additional fusion-positive tumors, all of which were of the invasive mucinous subtype. Mechanistically, CD74-NRG1 leads to extracellular expression of the EGF-like domain of NRG1 III-β3, thereby providing the ligand for ERBB2-ERBB3 receptor complexes. Accordingly, ERBB2 and ERBB3 expression was high in the index case, and expression of phospho-ERBB3 was specifically found in tumors bearing the fusion (P < 0.0001). Ectopic expression of CD74-NRG1 in lung cancer cell lines expressing ERBB2 and ERBB3 activated ERBB3 and the PI3K-AKT pathway, and led to increased colony formation in soft agar. Thus, CD74-NRG1 gene fusions are activating genomic alterations in invasive mucinous adenocarcinomas and may offer a therapeutic opportunity for a lung tumor subtype with, so far, no effective treatment. CD74–NRG1 fusions may represent a therapeutic opportunity for invasive mucinous lung adenocarcinomas, a tumor with no effective treatment that frequently presents with multifocal unresectable disease.